Strategi Pemerintah Taiwan dalam Meningkatkan Ekspor Agrikultur melalui Economic Cooperation Framework Agreement (ECFA) - Pramesti, Azalia Ayu; Purbantina, Adiasri Putri (Department of International Relations, Brawijaya University, 2021)
The relationship between China and Taiwan since separating in 1949 continues to fluctuate, particularly with the One China Policy. However, despite the political tension between the two, they have close bilateral economic ties relations, where China is Taiwan's largest trading partner. China and Taiwan signed an agreement entitled